Implementation of Direct Learning Strategy with Demonstration Method in Physical Education in Developing Students' Motor Skills in Elementary School - Firmansah, Deri (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This study aims to analyze the implementation of direct learning strategies with demonstration methods in physical education in developing students' motor skills in elementary schools. This research method uses a qualitative case study approach. The research subjects consisted of physical education, sports, and health teachers and fifth-grade students. Data were collected through interviews, participant observation, and documentation. Data analysis used Miles and Huberman which included data reduction, data presentation, and drawing conclusions. Data validity testing was carried out through triangulation of sources and techniques. The results of the study indicate that direct learning strategies with demonstration methods implemented systematically through providing clear examples of movements, repeated practice, and direct feedback are effective in improving the quality of students' motor skills, especially in the aspects of coordination, balance, and movement accuracy. In addition to impacting psychomotor aspects, the implementation of this strategy also improves students' affective aspects, such as self-confidence, courage to try, and active participation in learning. The research findings confirm that direct learning strategies based on demonstrations are in line with the developmental characteristics of elementary school students who are at the concrete operational stage, and are relevant as an effective and contextual approach to physical education learning.